Digitaler Distanzunterricht an Grundschulen - eine Analyse - Marita Katharina Wambach-Schulz (IU Internationale Hochschule, 2022)
– The early phase of the corona crisis began with the outbreak of the SARS-CoV-2 virus at the beginning of 2020 (Blom/Möhring,2021, p. 476). As a result, the everyday work of parents with school children changed from then on (Datenreport, Laß, 2021, p. 484). Work for families and teachers in times of daycare and school closures mutated from traditional-analogue face-to-face teaching to a field of tension between home office, homeschooling and digital distance teaching. Against this background, the analysis presented here is particularly relevant and topical. Thus, the effects of distance learning on pupils in the area of schools, especially primary schools during the school closures caused by the pandemic, are examined. The main expectation-generating research question is: How can the impact of distance learning during pandemic school closures on the learning of primary school students in the 1-4 grade cohort be assessed? The aim of this analysis is to relate the potential of digital distance learning to 'good' teaching according to Helmke (2006/2007). Future reasons for distance digital teaching could be new pandemic and other illnesses on the part of pupils and teachers. Therefore, this analysis is based firstly on findings from a database of existing secondary analyses of the early phase of the pandemic. Secondly, the analysis provides insight into an empirical-quantitative primary analysis of a student project in the summer semester of 2021 at the International University of Applied Sciences in Düsseldorf. Taking up the explosive nature of the topic in scientific studies in the future finds relevance to each other due to the presumably expected predominantly deteriorated performance of school-age children in Germany. According to the Ifo Institute, Munich (2021), there is hardly any other EU country where schools have been closed for as long as in Germany. The evaluation results of the primary analysis of the student group could surprise in some result aspects. This touched on the answer categories of the open-ended questions with statements of interest from the interviewed teachers at the three affected primary schools
Keywords: 300; Coronakrise; pandemiebedingte Schulschließungen; Distanzunterricht; Homeschooling; "guter" Unterricht